Sex differences in the association between composite dietary antioxidant index and hyperlipidemia: Insights from NHANES - Xiaofan Miao; Bixia Li; Zhixian Zhu; Tao Yang (PLoS ONE, 2025)
Background Previous studies have shown that both the composite dietary antioxidant index (CDAI) and sex are strongly associated with a variety of cardiovascular diseases, but sex differences between CDAI and hyperlipidemia are unknown. Objective This study utilized data from the National Health and Nutrition Examination Survey (NHANES) to investigate the sex differences between CDAI and hyperlipidemia. Method We calculated the CDAI of the six dietary antioxidants using data from NHANES, explored the relationship between CDAI and the prevalence of hyperlipidemia using multivariate logistic regression analysis, and analyzed for potential nonlinear associations using restricted cubic spline. Finally, the association between CDAI and hyperlipidemia was further explored using multivariate logistic regression in different genders. Results The study included a total of 34,754 participants with a mean age of 47.04 years, of whom 49.37% were man. In a fully adjusted multivariable binary logistic regression model, CDAI was negatively associated with the prevalence of hyperlipidemia (OR = 0.99, 95% CI:0.98–0.99). In addition, participants in the highest quartile had a lower risk of hyperlipidaemia compared with the lowest quartile of CDAI (OR = 0.83, 95%CI: 0.76–0.92). We also found a non-linear relationship (non-linear P = 0.003, Inflection point = -0.179). Finally, we found that the association between CDAI and the prevalence of hyperlipidemia was significantly stronger in the female population than in the male population (P for interaction <0.05). Conclusion Our study highlights the L-shaped association between CDAI and the prevalence of hyperlipidemia in the general adult population. In addition, this association was more significant in the female population than in the male population.